Repeat Whole Brain Radiation Therapy with a Simultaneous Infield Boost: A Novel Technique for Reirradiation. (26th May 2014) - Hall, William A.; Prabhu, Roshan S.; Crocker, Ian R.; Dhabban, Anees; Ogunleye, Tomi; Kandula, Shravan; Jiang, Xiaojun; Curran, Walter J.; Shu, Hui-Kuo G.
Abstract : The treatment of patients who experience intracranial progression after whole brain radiation therapy (WBRT) is a clinical challenge. Novel radiation therapy delivery technologies are being applied with the objective of improving tumor and symptom control in these patients. The purpose of this study is to describe the clinical outcomes of the application of a novel technology to deliver repeat WBRT with volume modulated arc therapy (VMAT) and a simultaneous infield boost (WB-SIB) to gross disease. A total of 16 patients were initially treated with WBRT between 2000 and 2008 and then experienced intracranial progression, were treated using repeat WB-SIB, and were analyzed. The median dose for the first course of WBRT was 35 Gy (range: 30–50.4 Gy). Median time between the initial course of WBRT and repeat WB-SIB was 11.3 months. The median dose at reirradiation was 20 Gy to the whole brain with a median boost dose of 30 Gy to gross disease. A total of 2 patients demonstrated radiographic disease progression after treatment. The median overall survival (OS) time from initial diagnosis of brain metastases was 18.9 months (range: 7.1–66.6 (95% CI: 0.8–36.9)). The median OS time after initiation of reirradiation for all patients was 2.7 months (range: 0.46–14.46 (95% CI: 1.3–8.7)). Only 3 patients experienced CTCAE grade 3 fatigue. No other patients experienced any ≥ CTCAE grade 3 toxicity. This analysis reports the result of a novel RT delivery technique for the treatment of patients with recurrent brain metastases. Side effects were manageable and comparable to other conventional repeat WBRT series. Repeat WB-SIB using the VMAT RT delivery technology is feasible and appears to have acceptable short-term acute toxicity. These results may provide a foundation for further exploration of the WB-SIB technique for repeat WBRT in future prospective clinical trials.